Gender Identity Ambiguity in the Novel Pasung Jiwa by Okky Madasari - Sari, Selvia Aniffah; Liliani, Else; Telaumbanua, Ester Anugrah (PT FORMOSA CENDEKIA GLOBAL, 2024)
English This study examines the gender identity confusion of Sasana's character in the novel Pasung Jiwa by Okky Madasari. The objectives of this research are; (1) to identify the obstacles faced by Sasana in forming her gender identity, (2) to identify the steps taken by Sasana in strengthening her gender identity. The approach used in this research is descriptive qualitative analysis with Stuart Hall's concept of identity as a process of being and becoming. The results of this study show that the concepts of masculinity, femininity, and the assessment of identity by others, as well as body identity are factors in Sasana's gender identity ambiguity. The steps taken by Sasana's character to deal with this ambiguity is through the process of her life journey, traits, attitudes, and behaviors to resemble women. In the end, Sasana gained full confidence in herself with the identity she wanted to look like a woman and Sasana finally got the support from the mother figure she had been longing for.